Strategi Peningkatan Kinerja UMKM Melalui Penerapan Total Quality Management (TQM) Berbasis Digital dalam Sistem Manajemen Operasional - Sy, Muhtarrom Naufal; Okta Sari Heppy Putri; Lusiana (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze strategies for improving MSME performance through the implementation of Digital-Based Total Quality Management (TQM) in operational management systems. The research employs a qualitative approach using a systematic literature review of articles published between 2020–2026 sourced from Google Scholar, Garuda, DOAJ, and accredited SINTA journals. The selection process followed the stages of identification, screening, eligibility, and inclusion, resulting in 17 eligible articles. Data were analyzed using content analysis and narrative synthesis to construct an integrative conceptual model. The findings indicate that TQM principles enhance quality stability and customer satisfaction but require digital support for systematic performance measurement. The integration of digital systems enables real-time data-driven decision-making. The study concludes that the synergy between TQM and digitalization improves efficiency, productivity, competitiveness, and long-term sustainability of MSMEs